Pengaruh Kualitas Informasi Akun Instagram @Kotajakartapusat Terhadap Citra Pemerintah - Novella Spania Putri Anggraeni; Muhammad Al Assad Rohimakumullah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This research was conducted to determine the effect of the information quality of the @kotajakartapusat Instagram account on the image of the Central Jakarta Administrative City Government. The research method uses quantitative survey methods and this type of research is causality. Sampling used a non-probability sampling method with purposive sampling of 99 respondents. The results showed that from the results of partial hypothesis testing (T test) there was a significant effect of Information Quality (X) Instagram account @kotajakartapusat on the City Administration City Government's Image (Y) significantly by tcount 9.382 â‰¥ 1.985 ttable value and significance value 0.000 â‰¤ 0.05 , this means that Ho is rejected and Ha is accepted. The conclusion of the study is that the influence of the information quality of the Instagram @kotajakartapusat account is very good on the image of the central Jakarta administrative city government.. Keywords: Central Jakarta Administration City Government, Image, Information Quality, Instagram